POLA KOMUNIKASI ORGANISASI DALAM MENINGKATKAN EKSISTENSI KOMUNITAS MARGA PARNA DI KOTA BATAM ( Studi Kasus Komunitas Marga Parna Di Batu Aji Kota Batam ) - Mendrofa, Aperian Jaya; Syafii, Muhammad (LPPM Universitas Putera Batam, 2019)
Ethnic Batak in the city of Batam consisting of several clans. One of them is the Marga Parna. With the existence of various Marga in Parna consisting of 50 Marga, in establishing friendship and maintaining its culture, Marga Parna formed an organization called the Marga Parna association various activities carried out in the organization of the Marga Parna association. This study aims to determine the patterns of organizational communication that occur within the Marga Parna group in increasing existence in the city of Batam. This research uses descriptive qualitative approach with the theory of organizational structure and communication patterns. The results of this study are the communication patterns that occur in the Marga Parna group in increasing excellence very well, namely communication patterns that occur routinely are wheel communication patterns, circle communication patterns, Y communication patterns, and star communication patterns, while less than maximum communication patterns occur within the Marga Parna group is the communication pattern of the Chain.